POTENSI EKOWISATA DI KAWASAN KONSERVASI KEPULAUAN SOMBORI KABUPATEN MOROWALI - Lambaniga, Otlinda Cahyani; Franklin, Papia J.C.; -, Suryono (SPASIAL, 2021)
Tourism in Indonesia is one of the important factors that support the development of an area in terms of economy, social or environment. In Central Sulawesi Province, especially Morowali Regency, there is a myriad of potentials that can become a pillar of regional development, one of which is in the tourism sector, namely the Sombori Islands Conservation Area which is a marine conservation area of 41,341 hectares. Composed of a group of natural islands with various potential tourist attractions. The purpose of this study was to determine the characteristics of the Sombori Islands Conservation Area and to examine the potential possessed by tourist destinations in the Sombori Islands Conservation Area with ecotourism directions. Data collection is divided into primary and secondary data, obtained through literature and policy studies, observations, interviews, documentation, and questionnaires distributed to selected respondents. This research was conducted with a descriptive quantitative approach, through Descriptive Analysis and ADO-ODTWA, to show the value of 4A namely Attraction, Amenities, Ancilliary and Accessibility. The results of this study identify the characteristics of the Sombori Archipelago Conservation Area which is composed of a group of karst islands, rock cliffs, white sandy beaches and "warehouses" of tourism potential, which are divided into 8 tourism potentials namely Allo Cave, Diamond Cave, Mata Air Kiri, Pulau Kayangan, Kokoh Island, Kayangan and Narinta Peaks, Sombori Lagoon and Mini Blue Hole and the index of the potential value of the 4 components supporting tourism objects in the Sombori Islands Conservation Area reached 83.41%, which means it is included in the category of high potential classification.Keywords: Tourism Potential, Sombori Conservation Area